Investigation of the household hazardous waste stream in a Hellenic municipality. (1st January 2014) - Kontogianni, Stamatia; Karagiannidis, A.; Logothetis, D.; Alexiou, G.
Hazardous waste (HW) in small quantities generated by households is often dumped into the mixed household waste. A variety of chemicals was recorded during a field research presented in the present paper. Aspects analysed in this work contribute to the categorisation of household hazardous waste (HHW) and quantification of them since lack of generation and composition data was noted in Greece. Towards that a field research was organised in a Hellenic municipality. Raw data were collected; 4.27 kg paint household-1 y-1, were found to be disposed in the municipality waste bins. The overall quantity is small compared to other waste streams nevertheless the impact in local environmental conditions and citizens' health are considered to be high. Results outcome of this research will be used to pave the way towards organisation of an HHW management plan, in order to lead those waste fractions to safe and sustainable management paths.